2012
DOI: 10.1159/000335005
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Preaxial Polydactyly Is Influenced by Modifying Genetic Elements and Is Not Maintained by Chromosomal Inversion in an Avian Biomedical Model

Abstract: Polydactyly (Po) is a common mutation found in many vertebrates. The UCD-Po.003 congenic chicken line was previously characterized for Po inheritance (autosomal dominant) and the mutation was mapped to chromosome 2p. Here, we describe for the first time the range and variability of the phenotype in this congenic line. Further, we studied the hypothesis that a chromosomal inversion was responsible for the maintenance of a large (6.3 Mb) candidate gene region. Fluorescence in situ hybridization employing BACs en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 115 publications
0
7
0
Order By: Relevance
“…Kalsoom et al 2013 have recently identified a novel zinc-finger gene ( ZNF141 ) associated with autosomal-recessive postaxial polydactyly type A through whole-genome sequencing combined with homozygosity mapping and array comparative genomic hybridization analysis. These studies found the gene for one polydactyly allele/locus, but the molecular mechanism and other polydactyly alleles/loci remain incompletely understood (Robb and Delany 2012). …”
mentioning
confidence: 99%
“…Kalsoom et al 2013 have recently identified a novel zinc-finger gene ( ZNF141 ) associated with autosomal-recessive postaxial polydactyly type A through whole-genome sequencing combined with homozygosity mapping and array comparative genomic hybridization analysis. These studies found the gene for one polydactyly allele/locus, but the molecular mechanism and other polydactyly alleles/loci remain incompletely understood (Robb and Delany 2012). …”
mentioning
confidence: 99%
“…In the present study, the ZRS in GGA2 was sequenced in Beijing You chickens, and no other mutations except for SNP rs80659072 were detected, suggesting that the ZRS sequence is highly conserved [30]. The association analysis showed the G/T polymorphism of rs80659072 was significantly associated with polydactyly in the mass Beijing You population ( P <0.0001).…”
Section: Discussionmentioning
confidence: 70%
“…Zhang et al [4] documented that polydactyly phenotypes in European and Chinese chickens were caused by two closely located but independent mutation events. Robb et al [30] conducted an inheritance analysis of the phenotypic variation in a congenic polydactyly chicken line and suggested that additional modifying genetic elements located outside of the ZRS could impact the preaxial polydactyly phenotype. Besides, in Dorking, Bouldin and Harfe [32] disclosed that preaxial polydactyly was initiated by the up-regulation of fibroblast growth factor 4 ( Fgf4 ) expression instead of Shh .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic chick embryo model (see Stern [5]), with its in ovo easy access, provides great value in this regard [6][10]. The utility of the chick embryo model was further improved by the availability of the chicken reference genome sequence [11], advanced tools and high-throughput technologies, as well as the existence of well-phenotyped developmental mutations [4], [12]–[14]. Such advantages led to the National Institute of Health recognition of the chicken as a model organism for biomedical research (http://www.nih.gov/science/models/gallus/).…”
Section: Introductionmentioning
confidence: 99%